Aktivitas insektisida ekstrak Piper aduncum dan Aglaia odorata terhadap Plutella xylostella (Linnaeus) (Lepidoptera: Plutellidae): Insecticidal activity of Piper aduncum and Aglaia odorata extracts on Plutella xylostella (Linnaeus) (Lepidoptera: Plutellidae) - heviyanti, Maria; Dadang; Sartiami, Dewi; Kusumah, Yayi Munara; Purwantiningsih (Perhimpunan Entomologi Indonesia, 2025)
One of the main problems in the cultivation of Brassicaceae vegetable plants is the attack of diamondback moth Plutella xylostella (Linnaeus). Extracts of Piper aduncum and Aglaia odorata have the potential to be used as botanical insecticides because they contain compounds that are toxic to insects. This study aims to evaluate the toxicity and feeding inhibition activity of hexane-extract of P. aduncum fruits and methanol-extract of A. odorata twigs against second instar larvae of diamondback moth. Extraction was carried out using the maceration method with a powder-to-solvent ratio of 1:10 (w/v). The diamondback moth insects used were from colonies reared in the laboratory. The lethal effect test was conducted using the leaf-dip method with test concentrations equivalent to LC15, LC35, LC55, LC75, LC95, and a control. The feeding inhibition test was conducted using the choice-test method with test concentrations equivalent to LC15, LC35, LC55, and a control. The results show that the hexane-extract of P. aduncum fruit is more toxic to second instar P. xylostella larvae than the methanol-extract of A. odorata twigs based on the probit analysis value of the relationship between concentration and mortality. The LC50 and LC95 values of P. aduncum extract were 0.07% and 0.14%, respectively, while the LC50 and LC95 values of A. odorata extract were 1.63% and 4.72%. Additionally, P. aduncum and A. odorata extracts also exhibited feeding against diamondback moth at concentrations of 0.07% and 1.77%, respectively. The combined effects of direct toxicity and feeding inhibition contributed to the mortality of the test insects. Thus, these two extracts, escpecially P. aduncum extract wich demonstrated higher effectiveness, have a great potential as botanical insecticides for controlling diamondback moth in Indonesia.